Economic Empowerment of Women through Micro-enterprises: A Case Study of Parbat District of Nepal - Dhaubhadel, Sarita (International Research Journal of MMC, 2022)
Micro-enterprises are small-scale business which is supported by governmental or non-governmental micro-credit program. Such enterprises are mostly run by the low-income group. It is supportive to manage the daily need of people. The study was conducted with the main objective to identify the economic empowerment of women through micro-enterprises. The study was conducted in the Parbat district of Nepal among the 384 women who were involved in the micro-enterprises. The study found that in total 96% of women agreed that they were able to support their family’s basic needs through the income of micro-enterprise. Similarly, 95% of women participants accepted that their economic access was increased through micro-enterprise.